Community Structure of Fishes the Association with Seagrasses at Bama Beach, Baluran National Park, Situbondo, East Java - Setyanto, Arif; Andriani, Dina; Sulkhani Yulianto, Eko; Tumulyadi, Agus; Bintoro, Gatut; Djoko Lelono, Tri; Adhihapsari, Wirastika; Nur Hidayah, Lisa; Isdianto, Andik; Zakiyah, Umi; Lanudia Fathah, Aulia; Kurnia Wardana, Novar; Mahardika Putri, Berlania (Journal of Marine and Coastal Science, 2024)
Seagrass bed has an important role for biota in waters. The existence of fish in seagrass is influenced by other ecosystems close to seagrass, such as mangroves and coral reefs. This study focuses on fish associated with seagrass in Bama Beach. The data include seagrass coverage and the number of fish for the Diversity, Uniformity, and Dominance. The study was carried out on March 15 to 20, 2018 using the Underwater Visual Census. Results show that seagrass cover was highest in seagrass stations near mangroves (62,66%), while at stations near coral reefs was 37,66. The composition of fish associated with seagrass near mangroves was 361 individuals, while near reefs was 1.454 individuals. The values of diversity, uniformity, and dominance of fish associated with seagrass near mangroves are 2,62; 0,88; and 0,09 respectively while those associated with coral reefs have values of 2,93; 0,85; and 0,06. Family Aulostomidae was dominant in the morning at the station near mangroves, and in the afternoon was dominated by Apogonidae. At the station near coral reefs, the Family Pomacentridae was dominant both in the morning and afternoon. The seagrass conditions in this study are in the healthy category with quite diverse fishes. The level of fish diversity in seagrass was influenced by habitats associated with seagrasses than seagrass cover levels. The condition of Bama Beach as a conservation area is quite good, but the activity of tourists around the coastline must be monitored to maintain the environment.